Investigation of shared micromobility preference for last-mile travel on shared parking lots in city center. (January 2023) - Hong, Doosun; Jang, Sunghoon; Lee, Chungwon
Highlight: A new context of last-mile travel after parking at shared parking lots in the city center. A stated preference experiment including uncertainty in availability of shared micromobility. Identification of substitution between shared micromobility modes to travelers' preference. Part-worth utility approach quantifying non-linear marginal effects of explanatory variables. Impact of latent perceptions for shared micromobility systems on choice behavior. Abstract: This study explores travelers' preference for shared micromobility in the context of last-mile travel from shared parking lots to their final destination in the city center. Based on the results of the stated preference experiment and error component logit model incorporating latent variables, we found that the preference for shared micromobility is affected by the uncertainty of availability as well as both travel time and fare. More specifically, our alternative-specific part-worth utility approach shows that their marginal effects are non-linear, and this suggests several policy implications. Also, we found that there is a significant substitution between shared micromobility modes. Furthermore, various latent perspectives, including safety and management concerns of shared micromobility, have significant impacts on the preference.